Affinity Purification and Characterization of a G-Protein Coupled Receptor, Saccharomyces cerevisiae Ste2p - Lee, Byung-Kwon (2007)
We present an example of expression and purification of a biologically active G protein coupled receptor (GPCR) from yeast. An expression vector was constructed to encode the Saccharomyces cerevisiae GPCR α-factor receptor (Ste2p, the STE2 gene product) containing a 9-amino acid sequence of rhodopsin that served as an epitope/affinity tag. In the construct, two glycosylation sites and two cysteine residues were removed to aid future structural and functional studies. The receptor was expressed in yeast cells and was detected as a single band in a western blot indicating the absence of glycosylation. Ligand binding and signaling assays of the epitope-tagged, mutated receptor showed it maintained the full wild-type biological activity. For extraction of Ste2p, yeast membranes were solubilized with 0.5 % n-dodecyl maltoside (DM). Approximately 120 μg of purified α-factor receptor was obtained per liter of culture by single-step affinity chromatography using a monoclonal antibody to the rhodopsin epitope. The binding affinity (Kd) of the purified α-factor receptor in DM micelles was 28 nM as compared to Kd = 12.7 nM for Ste2p in cell membranes, and approximately 40 % of the purified receptor was correctly folded as judged by ligand saturation binding. About 50 % of the receptor sequence was retrieved from MALDI-TOF and nanospray mass spectrometry after CNBr digestion of the purified receptor. The methods described will enable structural studies of the α-factor receptor and may provide an efficient technique to purify other GPCRs that have been functionally expressed in yeast.